PENGARUH INFLASI, LIKUIDITAS, VARIABILITAS LABATERHADAP BETA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010 - 2013 - Ridwan, Nur; Hasanah, Nuramalia (Jurnal Ilmiah Wahana Akuntansi, 2015)
This study aimed to determine the influence of inflation,liquidity, andearnings variabilityon thestock beta. The dependent variable in this study isstock betaand the independent variables in this research areinflation, liquidity, andearnings variability. inflation is measured by consumer price index, liquidity is measured by divisioncurrent assetwith number of current liability, andearnings variabilityis measured with deviation standard from price earning ratio. This study took a sample of mining companies listed in Indonesia Stock Exchange during the years 2010-2013. The data obtained by purposive sampling techniques and using multiple regression analysis. Simultaneous hypothesis testing result show that inflation, liquidity, andearnings variability simultaneously affectthestock beta. The partial hypothesis test result show that earnings variability have a significant affect thestock betawhileinflation and liquidity don’t affect significant thestock price. Keywords: inflation, liquidity, earnings variability, stock beta